2012
DOI: 10.1080/09585192.2012.743477
|View full text |Cite
|
Sign up to set email alerts
|

Varieties of collaboration: the case of an Australian retail union

Abstract: Much has been written about varieties of collaboration and the interplay between conflict and collaboration in industrial relations. This paper explores the preconditions, processes and outcomes associated with the collaborative strategies of an Australian retail trade union: the Shop, Distributive and Allied Employees' Association. The data were collected from an extensive series of interviews with officials and organisers within the union across all Australian states. We find that despite taking a servicing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…However, in the long run, it is argued that while institutional support is important for codifying and establishing practice, the sustainability is linked to the quality of relationship being built. Price et al (2014) highlight that the institutional nature of the Australian system, with awards and standard minimums, provided a context where a union ideologically committed to collaboration was able to foster such relationships. Yet Cathcart (2014) highlights that the devil may often be in the detail of stakeholder approaches which on the surface appear to represent multiple interests but then use non-union partnership to pursue a heavily managerialist agenda.…”
Section: The Context Of Partnership Collaboration and Mutual Gainsmentioning
confidence: 97%
“…However, in the long run, it is argued that while institutional support is important for codifying and establishing practice, the sustainability is linked to the quality of relationship being built. Price et al (2014) highlight that the institutional nature of the Australian system, with awards and standard minimums, provided a context where a union ideologically committed to collaboration was able to foster such relationships. Yet Cathcart (2014) highlights that the devil may often be in the detail of stakeholder approaches which on the surface appear to represent multiple interests but then use non-union partnership to pursue a heavily managerialist agenda.…”
Section: The Context Of Partnership Collaboration and Mutual Gainsmentioning
confidence: 97%
“…A study conducted by Price, Bailey and Pyman in 2014 concluded that an environment in which unions are not forced to fight to represent members can be conducive to collaborative employment relations, particularly in industries where the parties do not adopt an adversarial stance (Price et al, 2014). Bluestone and Kochan (2014) agreed that the continuing fiscal crisis facing the commonwealth countries and its municipalities can provide the motivation for forging a fundamental change in public sector labour relations.…”
Section: Legacy Issues and Socio-political Factorsmentioning
confidence: 99%
“…Th ere is also empirical evidence that has emerged from Australian workplaces in support of a pluralist framework involving unions, non-union representation and/or direct involvement of employees (Holland et al 2009 ;Price et al 2014 ;Townsend et al 2014 ). We discuss this further in the next section.…”
Section: Attitudes and Behaviour Of Major Social Partners (Employersmentioning
confidence: 95%